Towards bright gamma-ray flash generation from tailored target irradiated by multi-petawatt laser - Prokopis Hadjisolomou; Tae Moon Jeong; Sergei V. Bulanov (Scientific Reports, 2022)
Abstract One of the remarkable phenomena in the laser-matter interaction is the extremely efficient energy transfer to $$γ $$ γ -photons, that appears as a collimated $$γ $$ γ -ray beam. For interactions of realistic laser pulses with matter, existence of an amplified spontaneous emission pedestal plays a crucial role, since it hits the target prior to the main pulse arrival, leading to a cloud of preplasma and drilling a narrow channel inside the target. These effects significantly alter the process of $$γ $$ γ -photon generation. Here, we study this process by importing the outcome of magnetohydrodynamic simulations of the pedestal-target interaction into particle-in-cell simulations for describing the $$γ $$ γ -photon generation. It is seen that target tailoring prior the laser-target interaction plays an important positive role, enhancing the efficiency of laser pulse coupling with the target, and generating high energy electron-positron pairs. It is expected that such a $$γ $$ γ -photon source will be actively used in various applications in nuclear photonics, material science and astrophysical processes modelling.